Postpartum Pain Management. Issue 1 (January 2022) - Wisner, Kirsten
Abstract : Postpartum pain is common and may interfere with a patient's selfcare and infant care. Untreated pain has been associated with postpartum depression, persistent pain, and higher use of opioids. Our maternity nursing expert, Dr. Wisner, provides a summary of a new American College of Obstetricians and Gynecologists Clinical Consensus guideline on pharmacologic pain management for acute perineal, uterine, and incisional pain in the postpartum period.